Political Connection for Sustainability: The Role of Ownership Type in Determining Management Compensation - Putri, Yani Prasetya; Kresnawati , Etik (Universitas Muhammadiyah Yogyakarta, 2024)
This study aims to examine whether there are differences in management team compensation of different ownership types and their role in moderating the effect of political connections on management team compensation. The population of this study were all companies listed on the IDX in 2018-2022 with sampling techniques using purposive sampling. The test results using the Fixed Effect Model show that there is no difference in management team compensation in different ownership types. On the other hand, the type of company ownership strengthens the influence of political connections on team compensation management. These results strengthen the notion that non-SOE companies utilize political connections to sustain by providing higher rewards.